Dissatisfaction and Discontinuation of Contact Lens Use among University Students in Lahore Pakistan - Hafiz Zaki Naeem; Muhammad Matee Ullah; Nubera Ahmed; Nauman Ismat Butt (Utan Kayu Publishing, 2026)
To assess the factors contributing to dissatisfaction and discontinuation of contact lens use among university students in Lahore Pakistan. This cross-sectional study was conducted at Superior University Lahore Pakistan. A total of 50 undergraduate students having a history of contact lens use followed by discontinuation, aged 18–25 years, studying in various disciplines, were enrolled using a non-probability consecutive sampling. Students who were actively using contact lenses were excluded. Informed consent was obtained prior to enrollment. Data were collected using a specially designed questionnaire consisting of three domains. The first domain included demographic information such as age and gender, along with details related to contact lens use. The second domain assessed factors related to dissatisfaction, while the third domain focused on contact lens discontinuation. Data were entered and analyzed using SPSS version 23. A total of 50 university students who had discontinued contact lens use were included (mean age 21.8 ± 1.7 years; 50% male). Soft extended-wear lenses were most commonly used (46%), and half of participants wore lenses on ≤2 days per month. Key complaints included discomfort (62%), handling difficulties (66%), dryness (66%), and ocular complications such as eye injuries (38%) and infections (32%). Most participants (72%) had discontinued lenses within the past few months, with 42% attributing their eye symptoms possibly to lens use. Despite discontinuation, over half (52%) indicated willingness to resume lens use in the future. In this dropout sample of university students, discomfort, handling difficulties, and ocular symptoms were frequently reported among previous contact lens users. These findings highlight factors associated with dissatisfaction and discontinuation. Future studies should employ multi-center designs, compare active users with dropouts, and use validated instruments to better understand patterns of contact lens use and discontinuation in Pakistan.